Subpellicular and flagellar microtubules of Trypanosoma brucei brucei contain the same alpha-tubulin isoforms (The Rockefeller University Press, 1987)
The cytoskeleton of the parasitic hemoflagellate Trypanosoma brucei brucei essentially consists of two microtubule-based structures: a subpellicular layer of singlet microtubules, which are in close contact with the cell membrane, and the flagellar axoneme. In addition, the cells contain a small pool of soluble tubulin. Two-dimensional gel electrophoretic analysis of the tubulins present in these subcellular compartments revealed two distinct electrophoretic isoforms of alpha- tubulin, termed alpha 1 and alpha 3. alpha 1-Tubulin most likely represents the primary translation product, while alpha 3-tubulin is a posttranslationally acetylated derivative of alpha 1-tubulin. In the pool of soluble cytoplasmic tubulin, alpha 1 is the predominant species, while the very stable flagellar microtubules contain almost exclusively the alpha 3-tubulin isoform. The subpellicular microtubules contain both isoforms. Neither of the two alpha-tubulin isoforms is organelle specific, but the alpha 3 isoform is predominantly located in stable microtubules.